2015
DOI: 10.1111/jen.12202
|View full text |Cite
|
Sign up to set email alerts
|

Using viable eggs to accurately determine the demographic and predation potential ofHarmonia dimidiata(Coleoptera:Coccinellidae)

Abstract: Life table parameters and predation rate of the coccinellid predator Harmonia dimidiata F. fed on Aphis gossypii Glover were determined at 25°C using the age‐stage, two‐sex life table. When the total number of eggs were included in our calculations, the intrinsic rate of increase (r), finite rate (λ), net reproductive rate (R0) and mean generation time (T) for H. dimidiata were 0.1354/day, 1.1450/day, 280.8 offspring and 41.6 day, respectively. These values were significantly different, however, only when viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 34 publications
2
53
0
Order By: Relevance
“…Results and Discussion Mou et al (2015) fail to consider that egg viabilities h x are closely related to N e /N, that is:…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations
“…Results and Discussion Mou et al (2015) fail to consider that egg viabilities h x are closely related to N e /N, that is:…”
Section: Methodsmentioning
confidence: 95%
“…It should be considered that initial eggs of parent population are a random sample and thus they were produced by females from different ages; thus, the egg viability of the parent population should not be different from that observed during the experiment. The high egg viability observed in the parent cohort compared with the low viability observed in the first generation would suggest that these eggs came from females of intermediate ages, where Mou et al (2015) observed the highest peak of hatch rate.…”
Section: Generation Timementioning
confidence: 95%
See 2 more Smart Citations
“…The relative humidity inside the plastic cylinders was monitored by a HOBO data logger equipped with a small diameter external sensor (Onset Computer Corporation, Bourne, MA, US). Because we had previously observed that K. paulula preferred to oviposit on pilose beggarticks and that the hatch rate varied with female age, newly hatched nymphs from a cohort of 114 eggs laid on pilose beggarticks within a 24-hr period were used to begin the life table study (Mou et al 2015). Newly hatched nymphs were transferred to individual plastic cylindrical rearing cages (20 cm in height, 7 cm in diameter and covered with 100 mesh nylon screen) and placed on a plastic pot (7.6 cm in diameter) containing one plant each of pilose beggarticks and trilobate wedelia.…”
Section: Life Table Studymentioning
confidence: 99%